DAMPAK SOSIAL PERKEMBANGAN BAKPIA DALAM INDUSTRI PARIWISATA DI PATHUK YOGYAKARTA - Luluk Nihayati (Pringgitan, 2020)
As a special food that has become an icon of a region, Bakpia is very important for people's lives, especially when viewed from an economic perspective. The existence of Bakpia has given a lot of blessings to the weak economy groups that are not absorbed into the formal sector. Thus, this study describes the Bakpia business unit along with individuals and the competency involved in it, Bakpia as a tourism industry, the economic implications of Bakpia, and the impact of its development on the Pathok community. This research is qualitative research, both positioned as a primary source and as part of the explanation in the effort to reconstruct the development of Bakpia. This causes the facts obtained from the resource persons to be agreed so that they meet the requirements to be part of the results. Related to economic studies, it is being discussed in the preparation of the study's thought flow. The consideration, namely the development of Bakpia changes and cannot be separated from the licensing of the informal city economic sector. Sectors that support economic actors are not enumerated by statistical data so that they are often considered as one of the main concerns of the city.Keywords: culinary, bakpia, tourism industry, social impact